Survey of ICT and Education in Africa : Sao Tome and Príncipe Country Report - Fall, Babacar (World Bank, Washington, DC, 2012)
This short country report, a result of larger Information for Development Program (infoDev) - supported survey of the Information and Communication Technologies (ICT) in education in Africa, provides a general overview of current activities and issues related to ICT use in education in the country. The government of Sao Tome does not consider ICT to be a priority sector, and there is currently no specific policy that addresses ICTs. Internet service is not yet liberalized, but there is some restructuring of telecommunications infrastructure underway.